Geometric and electronic properties of graphene-related systems : chemical bonding schemes - Tran, Ngoc Thanh Thuy; Lin, Shih-Yang; Lin, Chiun-Yan; Lin, Ming-Fa (CRC Press, 2018)
"Due to its physical, chemical, and material properties, graphene has been widely studied both theoretically and experimentally since it was first synthesized in 2004. This book explores in detail the most up-to-date research in graphene-related systems, including few-layer graphene, sliding bilayer graphene, rippled graphene, carbon nanotubes, and adatom-doped graphene, among others. It focuses on the structure-, stacking-, layer-, orbital-, spin- and adatom-dependent essential properties, in which single- and multi-orbital chemical bondings can account for diverse phenomena. Geometric and Electronic Properties of Graphene-Related Systems: Chemical Bonding Schemes is excellent for graduate students and researchers, but understandable to undergraduates. The detailed theoretical framework developed in this book can be used in the future characterization of emergent materials."--Provided by publisher
Keywords: Graphene -- Properties.; Nanostructures.; Chemical bonds.; Chemical structure.; Quantum chemistry.; elektronické knihy; electronic books